2013
DOI: 10.1016/j.ijmm.2013.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Legionella oakridgensis ATCC 33761 genome sequence and phenotypic characterization reveals its replication capacity in amoebae

Abstract: Legionella oakridgensis is able to cause Legionnaires` disease, but is less virulent compared to L. pneumophila strains and very rarely associated with human disease. L. oakridgensis is the only species of the family legionellae which is able to grow on media without additional cysteine. In contrast to earlier publications, we found that L. oakridgensis is able to multiply in amoebae. We sequenced the genome of L. oakridgensis type strain OR-10 (ATCC 33761).The genome is smaller than the other yet sequenced Le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
32
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 91 publications
0
32
0
Order By: Relevance
“…Indeed, host cell glycogen could be degraded to glucose by the action of the bacterial glucoamylase GamA (19,34). Further supporting the role of glucose as a nutrient for intracellular L. pneumophila, glucose uptake was found to be increased during the late phases of growth (33), and Legionella species-specific differences in their usages of glucose and serine as carbon substrates were suggested recently (35,36). However, the differential transfer of substrates during the different growth phases of L. pneumophila has not yet been directly shown.…”
mentioning
confidence: 86%
“…Indeed, host cell glycogen could be degraded to glucose by the action of the bacterial glucoamylase GamA (19,34). Further supporting the role of glucose as a nutrient for intracellular L. pneumophila, glucose uptake was found to be increased during the late phases of growth (33), and Legionella species-specific differences in their usages of glucose and serine as carbon substrates were suggested recently (35,36). However, the differential transfer of substrates during the different growth phases of L. pneumophila has not yet been directly shown.…”
mentioning
confidence: 86%
“…Recently, two human cases of Legionnaires' disease caused by L. oakridgensis were reported in France (3), showing that the bacteria are able to replicate inside human cells (1,(4)(5)(6)(7). Moreover, it was demonstrated that L. oakridgensis is able to multiply inside amoebae (4) and that the type IV secretion system is a key virulence factor; new virulence factors were also described (4).…”
mentioning
confidence: 99%
“…Moreover, it was demonstrated that L. oakridgensis is able to multiply inside amoebae (4) and that the type IV secretion system is a key virulence factor; new virulence factors were also described (4). In general, no additional cysteine is needed to grow L. oakridgensis on agar plates and extracel-lular glucose cannot be metabolized by the bacterium (4). For L. oakridgensis, it was demonstrated that the species is nonflagellated and that almost all flagellar regulon genes are absent, including the master regulator protein FleQ.…”
mentioning
confidence: 99%
See 2 more Smart Citations